Gandhi's Religion - Jordens, J. author. aut Link
IX, 283 p.
Keywords: This is the first systematic study of Mohandas Gandhi's conception of religion and of his personal religious practices to be based on the ninety volumes of his Collected Works. With a constant awareness of chronology, it focuses on Gandhi's own statements, revealing the considerable development of his ideas within a lasting and consistent ideological and moral framework. This biography of Gandhi as a Hindu discloses how he was influenced by, and reacted to, Hindu traditions, and why the Hindu establishment rejected him.